1979
DOI: 10.1098/rstb.1979.0005
|View full text |Cite
|
Sign up to set email alerts
|

An experimental electron microscopy study of afferent connections to the primate motor and somatic sensory cortices

Abstract: An experimental electron microscope (e.m.) study has been made of the termination of the afferent connections to the primate sensori-motor cortex. Following large, stereotaxically placed thalamic lesions, degeneration in the motor and somatic sensory cortices was studied at survival periods of 4 and 5 days. Degenerating thalamocortical terminals had asymmetric membrane specializations. In the motor cortex 89.5% made synapses on to dendritic spines, 9% on to dendritic shafts and 1.5% on to cell somata; in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…difference is suggested by published photomicrographs (Jones and Powell, 1970;Garey and Powell, 197 1;LeVay and Gilbert, Discussion 1976;Peters and Feldman, 1976;Sloper and Powell, 1978; Morphological observations Hersch and White, 198 1;McGuire et al, 1984; White and KelThalamic fibers terminating in layer IV of different regions of ler, 1987;LeVay, 1988;Enhanane and White, 1990; Czeiger cortex were generally similar, and differed markedly from terand White, 1993), the present study provides morphometric . Scatterplot showing Glu immunostaining over vesicle-containing regions in thalamocortical terminals (circles) and GABAergic terminals (triangles); regression lines are least squares fits.…”
Section: Light Microscopymentioning
confidence: 45%
“…difference is suggested by published photomicrographs (Jones and Powell, 1970;Garey and Powell, 197 1;LeVay and Gilbert, Discussion 1976;Peters and Feldman, 1976;Sloper and Powell, 1978; Morphological observations Hersch and White, 198 1;McGuire et al, 1984; White and KelThalamic fibers terminating in layer IV of different regions of ler, 1987;LeVay, 1988;Enhanane and White, 1990; Czeiger cortex were generally similar, and differed markedly from terand White, 1993), the present study provides morphometric . Scatterplot showing Glu immunostaining over vesicle-containing regions in thalamocortical terminals (circles) and GABAergic terminals (triangles); regression lines are least squares fits.…”
Section: Light Microscopymentioning
confidence: 45%
“…However, the paucity of axospinous synapses appears to be an actual feature of this connection because all but three contacts seen at the EM level were axodendritic. This is in spite of the fact that, similar to numerous projections that link different cortical areas of many species through axospinous projections (Jones and Powell, 1970;Lund and Lund, 1970;Sloper and Powell, 1979;Cipolloni and Peters, 1983;Innocenti, 1984;Fisken et al, 1985), the majority of the synapses formed between area 3a axons and unidentified area 2 neurons are axospinous (57%; Porter, 1991). Therefore, the particular population of neurons studied here appears to form fewer axospinous synapses with area 3a afferents than the overall population of area 2 neurons.…”
Section: Discussionmentioning
confidence: 56%
“…Conversely, they are the targets of the majority of intrinsic axon collaterals (Kisvardy et al, 1986;Gabbott et al, 1987;Elhanany and White, 1990;McGuire et al, 1991;White and Czeiger, 1991;Keller and Asanuma, 1993) and of inter-areal cortical afferents (e.g. Jones and Powell, 1970;Lund and Lund, 1970;Fisken et al, 1975;Sloper and Powell, 1979;Cipolloni and Peters, 1983;Ichikawa et al, 1985;Porter and Sakamoto, 1988) arising from pyramidal neurons in many cortical areas of different species. A handful of studies have focused on the specific patterns of synaptic interactions between the local axon collaterals of pyramidal neurons and their target cells in various regions of the cortex.…”
mentioning
confidence: 99%
“…One necessary structural prerequisite for the veto mechanism is that the spine should receive input from two different types of synapses. Electron microscopic studies have shown that 5-20 % of all spines are thought to carry two different types of synapses, one GABA (y-aminobutyric acid)-ergic and thought to be inhibitory, the other excitatory (Jones & Powell, 1969;Peters & Kaiserman-Abramof, 1970;Sloper & Powell, 1979;Koch & Poggio, 1983;Beaulieu & Colonnier, 1985;Somogyi & Soltesz, 1986). However, previous studies either did not identify the source of the synapse, or did not quantify the number of dual inputs in the case of identified geniculocortical synapses (Freund et al 1985b), which form between 5 and 30 % of synapses in layer 4 (Garey & Powell, 1971;LeVay & Gilbert, 1976).…”
Section: Introductionmentioning
confidence: 99%